Experimental studies on engine test system based on virtual instrument technology - YE Sheng; HE Yong; XU Xiao-ming (浙江大学学报. 农业与生命科学版)
Virtual Instrumentation (VI) is becoming a popular tool in measurement, test and automation as a result of rapid development of computer technology. In this paper, a engine test experimental system comprised of computer, DAQ Card PCI-6024E board, and other components, is presented. The signal output from sensors are transmitted to PCI-6024E board by conditioning circuits, and two-circuit control mode of throttle and hydrovalve with closed loop drive by direct digital control has been proposed. The control signals based on the incremental PID control algorithm are sent out from PCI-6024E board, and they control the throttle and hydrovalve by pulse width modulation drove circuits. The accuracy and stability of the whole control system has been proved satifactory. The system software has been developed by LabVIEW, which offers the system a lot of merits, such as friendly user interface, cost of development, short development period, and flexible functional-extension, etc.